Analisis Rasio Keuangan Yang Berpengaruh Terhadap Return On Investment (ROI) Pada Koperasi Serba Usaha Di Kabupaten Boyolali Tahun 2011-2013 - Purnamasari, Dwi Kurnia; , Nur Achmad, S.E., M.Si (2015)
Koperasi Pegawai Republik Indonesia (KPRI) "MERAPI" KPRI Merapi is one entity that aims to improve the welfare of its members in the district Musuk boyolali district. The purpose of this study was to determine the development of the return on investment (ROI) on KPRI "Merapi", which in terms of financial ratios. Financial ratios used include liquidity ratios, solvency and profitability based on financial statement data per month from 2012 until 2014. The method used is multiple linear regression analysis, while analysis tools namely liquidity ratio as measured by the current ratio, solvency ratio measured by debt-to-equity ratio and to measure the profitability ratios with return on equity. his study uses these ratios due to the cooperative generally use the current ratio, debt to equity ratio and return on equity Based on the analysis and discussion, the return on investment (ROI) on KPRI "Merapi" the terms of the financial ratios including liquidity ratios, solvency and profitability experienced fluctuating results from 2012 until 2014.Where the current ratio of -0.349, does not have a significant relationship and negatively affect the return on investment, and debt to equity ratio of -0.746 have a significant relationship and negatively affect the return on investment, while the return on equity of 0,579 has a significant relationship and a positive effect on return on investment. So the return on investment is only a good effect on the return on equity while the current ratio and debt to equity does not have an influence on the return on investment.